The Educationalization of Student Emotional and Behavioral Health Alternative Truth - Sullivan, Teresa L. (Springer International Publishing, 2018)
This book examines the current political, social, and economic positions that push the responsibility for the emotional health of students onto schools. The context of recent education reform asks schools to mitigate adverse emotional health of students by developing and implementing broad programming, curriculum, and policies immersed in cognitive behavioral approaches. The design plan is intended to build resilience and develop strategies in students that will enable them to succeed despite adverse structural conditions. The swindle of education reform is that it deflects and blames families, youth, and the school system for the social ills of society. From the perspective of a thirty year Massachusetts educator and high school principal emerges an alternative reality that not only challenges decades of education reform entrenched in victim blaming but also exposes a serious responsibility gap.